The making of the first Korean president : Syngman Rhee's quest for independence, 1875-1948 - Yu, Yŏng-ik (University of Hawaiʻi Press, 2014)
The only full-scale history of Syngman Rhee's (1875-1965) early career in English was published nearly six decades ago. Now, in The Making of the First Korean President, Young Ick Lew uncovers little-known aspects of Rhee's leadership roles prior to 1948. In this richly illustrated volume, Lew delves into Rhee's background, investigates his abortive diplomatic missions, and explains how and why he was impeached as the head of the Korean Provisional Government in 1925.